Analisis Pengaruh Kedalaman Pemakanan terhadap Getaran dan Kekasaran Permukaan dalam Proses Pembubutan Baja AISI 4140 - Mudjijanto, Mudjijanto; Achmadi, Ali; Agustino, Agil (SIMETRIS, 2025)
This research was conducted to evaluate the effect of varying depth of cut on vibration levels and surface roughness during the turning process of AISI 4140 steel. The experiments were carried out using a lathe machine equipped with a carbide cutting tool, a spindle speed of 265 rpm, and a feed rate of 0.1 mm/rev. The depth of cut was varied at 0.5 mm, 1 mm, and 1.5 mm. Experimental results indicated that increasing the depth of cut significantly influenced the rise in vibration and surface roughness values. At a depth of 0.5 mm, the recorded vibration was 0.4 mm/s with a surface roughness (Ra) of 4.074 µm. Meanwhile, at depths of 1 mm and 1.5 mm, vibration increased to 1.1 mm/s and 1.8 mm/s, with surface roughness values of 4.216 µm and 5.758 µm, respectively. These findings suggest that greater depths of cut lead to higher cutting forces, which in turn elevate both vibration and surface roughness. Therefore, selecting appropriate machining parameters is crucial to achieving optimal surface quality in turning processes